Czy cała Puszcza Białowieska powinna być parkiem narodowym? - Zientarski, Jacek; Szmyt, Janusz (Leśne Prace Badawcze, 2017)
In Poland, the stormy discussion on the future of the Białowieża Forest has been ongoing already for a long time. The disputes are mostly focused on seeking answers to two questions: how to protect these unique forest ecosystems and whether forest management threatens their naturalness. The discussion has grown stronger after the recent, enormous outbreak of Ips ypographus in the Forest. The Białowieża Forest has been managed for years with no negative effect. However, antagonists of foresters blame forest management for degradation of the Forest’s ecosystems, which is caused by favoring the economic value of timber expected to be harvested in keeping with the management plans of 3 forest districts located in the Białowieża Forest. At any rate, such assumption, has nothing to do with reality. During this discussion the idea to extend the national park for all the Białowieża Forest revived. In this paper, we reviewed the economic, social and ecological dimensions which should be taken into consideration before making a decision on extending the Białowieża National Park. It should be underlined that the Park’s area is already under the strict protection; furthermore, 2/3 of the area of neighboring managed forests are under legal protection (the nature reserves, NATURA 2000, the so-called reference forests, etc.). All things considered, we cannot find any reasonable purpose (ecological, financial or social) for expanding the Park’s area from 10 500 ha (present status) to 62 500 ha (after extension). Also, we are convinced that sustainable forest management conducted in managed parts of the Białowieża Forest, which comprises the fulfillment of all forest functions and services, should not be perceived as a threat to naturalness of the Forest’s ecosystems.